Peritoneal Dissemination of Hepatoid Carcinoma of the Ovary Treated with Cytoreductive Surgery and Hyperthermic Intraoperative Intraperitoneal Chemotherapy - Pedro Antonio Cascales Campos; Jose Gil Martinez; Amparo Torroba; Francisco Machado; Pascual Parrila Paricio (Case Reports in Medicine)
Hepatoid carcinoma of the ovary (HCO) was first reported in 1987 in 5 cases of malignant ovarian tumors which were similar to hepatocarcinoma in the histological analysis. We report the first case in the literature of a patient diagnosed with HCO treated using HIPEC after extensive cytoreductive surgery, and we discuss the value of this therapeutical option in patients with HCO.